2020
DOI: 10.2478/aoas-2019-0064
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Meat from Female Fallow Deer (Dama Dama) and Roe Deer (Capreolus Capreolus) Hunted in Serbia

Abstract: Deer meat is a high quality and valuable food for human consumption. It has high nutritive value because of its high protein and heme iron content, and low levels of fats and saturated fatty acids. The aim of this study was to examine the quality parameters of meat from fallow deer and roe deer that were hunted in Serbia. Parameters studied were live weight, carcass weight, chemical composition of meat, color, fatty acid content of meat, volatile compounds, and sensory characteristics. The results obtained sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 32 publications
3
8
0
Order By: Relevance
“…In turn, Revilla et al [61] reported a higher concentration of SFA in the meat of cattle reared in the organic system compared with the conventional farming system. C16:0 and C18:0 acids are the dominant SFAs in red meat [23,24,52], which was demonstrated in the present study as well. No effect of stearic acid C18:0 on total cholesterol levels has been reported.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…In turn, Revilla et al [61] reported a higher concentration of SFA in the meat of cattle reared in the organic system compared with the conventional farming system. C16:0 and C18:0 acids are the dominant SFAs in red meat [23,24,52], which was demonstrated in the present study as well. No effect of stearic acid C18:0 on total cholesterol levels has been reported.…”
Section: Discussionsupporting
confidence: 87%
“…Foods in the human diet with a PUFA/SFA ratio below 0.45 are regarded as undesirable due to their potential effect of increasing blood cholesterol levels [82]. In the present study, the PUFA/SFA ratio in the meat of the conventionally reared fallow deer was similar to the value reported by Ivanović et al [24] for the musculus longissimus thoracis (LT) of fallow deer from Serbia. In turn, the ratio in the muscles of the organically farmed animals was higher than the value in meat from farmed and wild fallow deer (0.27) calculated by Daszkiewicz [52] and in beef and lamb muscles (0.11-0.37) [44].…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Despite the numerous advantages of wild game (nutritional, taste, health), its consumption in many countries in Europe, including Poland, Great Britain, Czech Republic, Croatia, Germany, Norway, and Sweden, is low. In recent years, it was from 0.2 to 1.1 kg/person/year [ 27 , 28 , 29 , 30 , 31 , 32 ], but only 2–4% of the population consumed this type of meat regularly [ 33 ]. Greater consumption was found among hunters and their families [ 34 , 35 ].…”
Section: Introductionmentioning
confidence: 99%